The Role of Financial Literacy and Peers in Financial Planning for Islamic Boarding School Students - Muhammad Maulana Iskhak; Umi Fitria; Margaretha Lasni Rhussary (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyse in depth the influence of financial literacy (X1) and peers (X2), both partially and simultaneously, on the financial planning of male and female students (Y) in the second year of Ulya at the Tanzilul Hakim Islamic Boarding School. This study uses a quantitative approach with a causal associative research type. The population and sample of this study are all 48 male and female students in class 2 Ulya, making this study a population study. Primary data were collected through questionnaires and analysed using Multiple Linear Regression Analysis with the help of the SPSS program, after undergoing classical assumption tests. The results of the hypothesis indicate that financial literacy and peers are suspected to have a positive and significant influence, both individually and collectively, on the financial planning skills of students. The results of this study are expected to provide valuable input for Islamic boarding schools to develop relevant financial education programmes to improve the financial planning skills of students.